2006
DOI: 10.1002/mus.20621
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise and creatine on myosin heavy chain isoform composition in patients with Charcot–Marie–Tooth disease

Abstract: It is not known whether myosin heavy chain (MHC) content changes in response to exercise training or creatine supplementation in subjects with Charcot-Marie-Tooth disease (CMT). Based on previous data, we hypothesized that resistance exercise and creatine would increase the percentage of type I MHC composition in the vastus lateralis muscle and that myosin isoform changes would correlate with improved chair rise-time in CMT subjects. To test this hypothesis, 18 CMT subjects were randomly assigned to either a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 43 publications
0
25
0
1
Order By: Relevance
“…In this respect, Cr seems to be effective in relieving symptoms, attenuating depression, and improving the quality of life in patients suffering from posttraumatic stress and fibromyalgia (Amital et al 2006a, b, c). Inborn or acquired diseases characterized by progressive loss of nervous-system cells such as Alzheimer's, Huntington's, Charcot-Marie-Tooth's and Parkinson's disease and amyotrophic lateral sclerosis (ALS) could be also potentially treated by Cr administration (Brewer and Wallimann 2000;Mazzini et al 2001;Tabrizi et al 2003;NET-PDN 2006;Smith et al 2006). These neurodegenerative disorders share common characteristics, including cerebral energy depletion (e.g., low brain Cr content), exacerbated oxidative stress and mitochondrial dysfunction.…”
Section: Brain Disordersmentioning
confidence: 98%
“…In this respect, Cr seems to be effective in relieving symptoms, attenuating depression, and improving the quality of life in patients suffering from posttraumatic stress and fibromyalgia (Amital et al 2006a, b, c). Inborn or acquired diseases characterized by progressive loss of nervous-system cells such as Alzheimer's, Huntington's, Charcot-Marie-Tooth's and Parkinson's disease and amyotrophic lateral sclerosis (ALS) could be also potentially treated by Cr administration (Brewer and Wallimann 2000;Mazzini et al 2001;Tabrizi et al 2003;NET-PDN 2006;Smith et al 2006). These neurodegenerative disorders share common characteristics, including cerebral energy depletion (e.g., low brain Cr content), exacerbated oxidative stress and mitochondrial dysfunction.…”
Section: Brain Disordersmentioning
confidence: 98%
“…The standard isokinetic testing method is not possible in cases of severe muscle weakness, when a patient is not even strong enough to move his/her limb and the lever arm against gravity. 91 Modifying isokinetic protocol to include the maximum speed, at which a muscle can generate torque, may serve as an indicator of the patient's functional potential because daily activities require the ability to develop tension at various velocities. With this method, both the limb and lever are weighed and gravity is compensated actively by the robot motor, which imposes a continuous isokinetic movement on the limb.…”
Section: Clinimetric Proprieties Of Isokinetic Dynamometrymentioning
confidence: 99%
“…99 Although supplemental dietary creatine was not found to improve muscle performance or muscle fiber size above that found with resistance training alone, 99 one morphologic study showed that creatine increased myosin heavy chain type II in HMSN patients undergoing resistance training, and that these changes correlated with improved muscle function as measured by chair rise time. 123 Another study of patients with HMSN showed that the initial strength increase with resistance training could be attributed to improved recruitment of motor units, with a subsequent contribution from muscle hypertrophy. 98 These findings were not replicated in DM.…”
Section: Mechanisms Of Improvementmentioning
confidence: 99%
“…Exercise-induced hyperpnea represents flow loading, and training in that regard could include either voluntary isocapnic hyperpnea (which is predominantly a flow-loading type of training) or threshold load training (which has been more frequently studied and may train both the pressure and flow-generating capacity of respiratory muscles). 70 Interventions that may facilitate or enhance the effects of exercise in patients with neuromuscular disease include provision of non-invasive ventilation prior to exercise for patients in whom alveolar hypoventilation may be responsible for the exercise limitation, 69 supplementation with creatine particularly in patients with HMSN 123 or dystrophies, 132 neuromuscular electrical stimulation and partial body weight support in patients with incomplete tetraplegia 118 steroids in DMD 72,133,134 and theophylline in ALS. 102,103 However, the balance of risks and benefits of the latter two options need to be weighed carefully, given the potential complications of long-term systemic steroids, and the narrow therapeutic window of theophylline.…”
mentioning
confidence: 99%